INTELLECTUAL PROPERTY PROTECTION IN BRANDING STRATEGIES OF LOCAL MSME PRODUCTS IN REJANG LEBONG REGENCY: OPPORTUNITIES AND CHALLENGES IN THE ERA OF GLOBALIZATION - Pefriyadi, Pefriyadi; Elfalahy, Lutfi; Indriyani, Dea; Maryadi, Jimmi (Multifinance, 2025)
Globalization presents new challenges for MSMEs in Rejang Lebong Regency in maintaining the competitiveness of local products, particularly in relation to Intellectual Property (IP) protection. Limited understanding and utilization of IP often weakens branding strategies that could strengthen the market position of local products at both the national and global levels. This study aims to analyze the level of MSME understanding of IP, identify the impact of IP protection on branding strategies, and examine the opportunities and challenges faced by MSMEs in utilizing IP in the era of globalization. Using a qualitative approach, data were collected through in-depth interviews with MSME actors and relevant government agencies. The object of this research consists of MSMEs in Rejang Lebong Regency that have the potential to develop local products with protected trademarks. The findings indicate that optimal IP protection contributes significantly to more effective branding strategies and reveals various opportunities and challenges in implementing IP to compete in the global market.